Cognate antigen stimulation generates potent CD8+ inflammatory effector T cells. - Hsueh-Cheng eSung; Sara eLemos; Patricia eRibeiro-Santos; Kateryna eKozryska; Florence eVasseur; Agnes eLegrand; Alain eCharbit; Benedita eRocha; Cesar eEvaristo (Frontiers in Immunology, 2013)
Inflammatory reactions are believed to be triggered by innate signals and have a major protective role by recruiting innate immunity cells, favoring lymphocyte activation and differentiation, and thus contributing to the sequestration and elimination of the injurious stimuli. Although certain lymphocyte types such as TH17 cells co-participate in inflammatory reactions, their generation from the naïve pool requires the pre-existence of an inflammatory milieu. In this context, inflammation is always regarded as beginning with an innate response that may be eventually perpetuated and amplified by certain lymphocyte types. In contrast, we here show that even in sterile immunizations or in MyD88 deficient mice, CD8 T cells produce a burst of pro-inflammatory cytokines and chemokines. These functions follow opposite rules to the classic CD8 effector functions since they are generated prior to cell expansion and decline before antigen elimination. As few as 56 CD8+ inflammatory effector cells in a lymph node can mobilize 107 cells in 24h, including lymphocytes, natural killer cells and several accessory cell types involved in inflammatory reactions. Thus, although inflammation modulates cognate responses, CD8 cognate responses also initiate local inflammatory reactions.